2022
DOI: 10.1001/jamahealthforum.2021.5111
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicare Mandatory Bundled Payment Reform With Joint Replacement Surgery Use for Beneficiaries With Alzheimer Disease and Related Dementias

Abstract: IMPORTANCE Medicare beneficiaries with Alzheimer disease and related dementias (ADRD) are a particularly vulnerable group in whom arthritis is a frequently occurring comorbidity. Medicare's mandatory bundled payment reform-the Comprehensive Care for Joint Replacement (CJR) model-was intended to improve quality and reduce spending in beneficiaries undergoing joint replacement surgical procedures for arthritis. In the absence of adjustment for clinical risk, hospitals may avoid performing elective joint replacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(50 reference statements)
2
3
0
Order By: Relevance
“…Consistent with our finding, one study found that CJR did not lead hospitals to decrease admission of high‐risk patients for joint replacement, although the definition of high‐risk patients in the previous studies was broad 14 . Focusing on Medicare enrollees with an arthritis diagnosis, another study also found that CJR did not lead hospitals to selectively avoid elective joint replacement for people with ADRD 30 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with our finding, one study found that CJR did not lead hospitals to decrease admission of high‐risk patients for joint replacement, although the definition of high‐risk patients in the previous studies was broad 14 . Focusing on Medicare enrollees with an arthritis diagnosis, another study also found that CJR did not lead hospitals to selectively avoid elective joint replacement for people with ADRD 30 …”
Section: Discussionsupporting
confidence: 84%
“…14 Focusing on Medicare enrollees with an arthritis diagnosis, another study also found that CJR did not lead hospitals to selectively avoid elective joint replacement for people with ADRD. 30 Our finding-no changes in the receipt of joint replacement under CJR among people with ADRD-may be potential because hospitals instead successfully reduced spending for these medically complex patients. The CJR model was associated with a $1029 reduction in total spending for people with ADRD (3.1% reduction from total spending in the pre-CJR period).…”
Section: Discussionmentioning
confidence: 80%
“…This study's findings are reassuring, but also highlight areas of improvement. First, the CJR Model has not led to reduced joint replacement surgeries in ADRD patients, a finding consistent with another recent study 8 . Second, this study demonstrates that the CJR Model has decreased spending among ADRD patients while maintaining quality of care, at least when evaluating 90‐day hospital readmissions, 90‐day emergency department use, 90‐day mortality, and functional status improvement as measured by ADL score.…”
supporting
confidence: 88%
“…The bundled payment system compensates providers for managing a patient's medical condition across the entire care continuum, encompassing all services, procedures, tests, medications, and devices involved in the treatment of specific conditions, such as lower extremity joint replacement. Lower extremity joint replacement bundle payment programs have demonstrated reduced episodic spending and resulted in maintained or improved quality of care in patients 105,106 …”
Section: Robotic Surgery For Cancermentioning
confidence: 99%